Developing multiscale and integrative nature–people scenarios using the Nature Futures Framework. Issue 4 (16th September 2020) - Pereira, Laura M.; Davies, Kathryn K.; den Belder, Eefje; Ferrier, Simon; Karlsson‐Vinkhuyzen, Sylvia; Kim, HyeJin; Kuiper, Jan J.; Okayasu, Sana; Palomo, Maria G.; Pereira, Henrique M.; Peterson, Garry; Sathyapalan, Jyothis; et al.
Abstract: Scientists have repeatedly argued that transformative, multiscale global scenarios are needed as tools in the quest to halt the decline of biodiversity and achieve sustainability goals. As a first step towards achieving this, the researchers who participated in the scenarios and models expert group of the Intergovernmental Science‐Policy Platform on Biodiversity and Ecosystem Services (IPBES) entered into an iterative, participatory process that led to the development of the Nature Futures Framework (NFF). The NFF is a heuristic tool that captures diverse, positive relationships of humans with nature in the form of a triangle. It can be used both as a boundary object for continuously opening up more plural perspectives in the creation of desirable nature scenarios and as an actionable framework for developing consistent nature scenarios across multiple scales. Here we describe the methods employed to develop the NFF and how it fits into a longer term process to create transformative, multiscale scenarios for nature. We argue that the contribution of the NFF is twofold: (a) its ability to hold a plurality of perspectives on what is desirable, which enables the development of joint goals and visions and recognizes the possible convergence and synergies of measures to achieve these visions and (b), its multiscale functionality for elaborating scenarios and models that can inform decision‐making at relevant levels, making it applicable across specific places and perspectives on nature. If humanity is to achieve its goal of a more sustainable and prosperous future rooted in a flourishing nature, it is critical to open up a space for more plural perspectives of human–nature relationships. As the global community sets out to develop new goals for biodiversity, the NFF can be used as a navigation tool helping to make diverse, desirable futures possible. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article. Abstrakte: Wetenskaplikes het herhaaldelik aangevoer dat transformerende, multiskaal globale scenario's nodig is as instrumente in die strewe om die agteruitgang van biodiversiteit te stop en volhoubaarheidsdoelwitte te bereik. As 'n eerste stap om dit te bereik, het die kundiges wat deelgeneem het aan die scenario's en modelle vir die kundige groep van die interregeringswetenskaplike beleid oor biodiversiteit en ekosisteemdienste (IPBES), 'n herhalende, deelnemende proses aangegaan wat gelei het tot die ontwikkeling van Nature Futures Framework (NFF). Die NFF is 'n heuristiese instrument wat verskillende, positiewe verhoudings van mense met die natuur in die vorm van 'n driehoek opneem. Dit kan beide gebruik word as 'n grensvoorwerp om deurlopend meer meervoudige perspektiewe oop te stel vir die skepping van wenslike natuurscenario's en as 'n uitvoerbare raamwerk vir die ontwikkeling van konsekwente natuurscenario's oor verskillende skale. Hier word die metodes beskryf om die NFF te ontwikkel en hoe dit inpas by 'n langertermynproses om transformerende, multiskale scenario's vir die natuur te skep. Ons argumenteer dat die bydrae van die NFF tweeledig is: a) die vermoë om 'n aantal perspektiewe te hou oor wat wenslik is, wat die ontwikkeling van gesamentlike doelwitte en visies moontlik maak en die moontlike konvergensie en sinergieë van maatreëls om hierdie te bereik en b) sy multi‐skaalfunksionering vir die uitwerking van scenario's en modelle wat besluitneming op relevante vlakke kan inlig, en dit toepaslik kan maak oor spesifieke plekke en perspektiewe op die natuur. As die mensdom sy doelwit van 'n meer volhoubare en welvarende toekoms met 'n bloeiende aard wil bereik, is dit van kritieke belang om 'n ruimte oop te maak vir meer plurale perspektiewe van mens‐natuur‐verhoudings. Aangesien die wêreldgemeenskap beoog om nuwe doelwitte vir biodiversiteit te ontwikkel, kan die NFF gebruik word as 'n navigasie‐instrument om verskillende, wenslike toekomste moontlik te maak. 摘要: 科学家们一再呼吁, 变革性的、多尺度的全球情景对于遏制生物多样性下降并实现可持续性目标, 是十分必要的工具。 作为实现这一目标的第一步, 生物多样性和生态系统服务政府间科学‐政策平台（Intergovernmental Science‐Policy Platform on Biodiversity and Ecosystem Services, 简称IPBES）情景和模型专家组的专家们采用迭代参与式的设计流程开发"自然未来框架"(Nature Futures Framework, 简称NFF)。 这是一款通过"三角形空间"捕获人与自然之间的多种多样的、积极关系的启发式工具。该框架既可以作为边界对象来不断开辟多元视角, 以创建理想的自然情景, 也可用于跨尺度地开发具有一致性自然情景的可行框架。 在这里, 我们的研究描述了开发"自然未来框架"（NFF）所采用的方法, 以及如何将其纳入到一个长期的过程中, 从而设计构建具有变革性的、多尺度的自然情景。我们的研究认为"自然未来框架"（NFF）的贡献体现在两个方面: a）对未来事物的想象或希望能够容纳多元观点, 这有助于制定共同的目标和愿景, 也有助于认识到实现这些目标和愿景的不同措施之间可能存在的趋同和协同作用；b）具有多尺度功能, 可用于详细说明情景和模型, 从而为相关层级的决策制定提供信息支持, 使其适用于特定地点和符合自然的视角。 如果人类要实现其根植于蓬勃发展的自然环境的更加可持续的、繁荣的目标, 就必须为更多的人与自然关系的多元视角开辟空间。随着国际社会开始制定全新的生物多样性目标, "自然未来框架"（NFF）可以作为促进其实现多样化的与理想的未来的导航工具。 Abstraite: Les scientifiques ont affirmé à plusieurs reprises que les scénarios mondiaux transformateurs et multi‐échelles sont des outils nécessaires aux efforts pour stopper le déclin de la biodiversité et atteindre les objectifs de durabilité. Dans un premier temps, les chercheurs ayant participé au groupe d'experts sur les scénarios et modèles de la Plateforme intergouvernementale scientifique et politique sur la biodiversité et les services écosystémiques (IPBES) se sont engagés dans un processus itératif et participatif qui a conduit au développement de 'Nature Futures Framework' (NFF). Le NFF est un outil heuristique qui capture les relations diverses et positives des humains avec la nature sous la forme d'un triangle. Il peut être utilisé à la fois comme un objet frontière pour élargir le champ des perspectives lors de la création de scénarios de nature souhaitables et aussi comme un cadre d'action pour développer des scénarios de nature cohérents à plusieurs échelles. Ici, nous décrivons les méthodes employées pour développer le NFF et comment cette démarche s'intègre dans un processus à plus long terme pour créer des scénarios transformateurs et multi‐échelles pour la nature. Nous soutenons que la contribution du NFF est double: a) sa capacité à avoir une pluralité de perspectives sur ce qui est souhaitable, ce qui permet de développer des visions et des objectifs communs tout en reconnaissant les possibles convergences et synergies des mesures nécessaires pour les atteindre et b), sa fonctionnalité multi‐échelles pour l'élaboration de scénarios et de modèles pouvant informer la prise de décision où nécessaire, la rendant applicable à des contextes et perspectives spécifiques sur la nature. Si l'humanité veut atteindre son objectif d'un avenir plus durable et plus prospère, ancré dans une nature florissante, il est essentiel de favoriser des perspectives plus diverses sur les relations homme‐nature. Alors que la communauté internationale se propose d'élaborer de nouveaux objectifs pour la biodiversité, le NFF peut être utilisé comme un outil de navigation permettant de créer des avenirs divers et souhaitables. αφηρημένη: Οι επιστήμονες έχουν επανειλημμένα υποστηρίξει πως παγκόσμια σενάρια με διαστάσεις μετασχηματιστικές και πολλών κλιμάκων, αποτελούν απαραίτητα εργαλεία στην προσπάθεια να σταματήσει η μείωση της βιοποικιλότητας και να επιτευχθούν οι στόχοι της βιωσιμότητας. Ως ένα πρώτο βήμα προς αυτό το στόχο, οι ειδικοί οι οποίοι συμμετείχαν στην εξειδικευμένη ομάδα για τη δημιουργία σεναρίων και μοντέλων, της ∆ιακυβερνητικής Πλατφόρµας Επιστήµης‐Πολιτικής για τη Βιοποικιλότητα και τις Οικοσυστηµικές Υπηρεσίες (IPBES), πήραν μέρος σε μία συμμετοχική διαδικασία, που μέσω της επανάληψης οδήγησε στη δημιουργία του Πλαισίου για τα Μέλλοντα της Φύσης (ΠΜΦ). Το ΠΜΦ είναι ένα ευρετικό εργαλείο το οποίο εξερευνάει ποικίλες θετικές σχέσεις των ανθρώπων με τη φύση, και υιοθετεί ένα τριγωνικό σχήμα. Μπορεί να χρησιμοποιηθεί και ως ένα καθοδηγητικό πλαίσιο για τη συνεχή διεύρυνση ποικίλων οπτικών κατά τη δημιουργία επιθυμητών σεναρίων για τη φύση, καθώς και ως ένα πλαίσιο με πρακτικές διαστάσεις που αποσκοπεί στην δημιουργία σενάριων για τη φύση σε διαφορετικές κλίμακες, με συνοχή ως προς το περιεχόμενο. Στο παρόν άρθρο περιγράφουμε τη μεθοδολογία που υιοθετήσαμε ώστε να αναπτύξουμε το ΠΜΦ, καθώς και το πως αυτό εντάσσεται σε μία μακροσκελή διαδικασία δημιουργίας σεναρίων για τη φύση με διαστάσεις μετασχηματιστικές και πολλών κλιμάκων. Υποστηρίζουμε πως η συμβολή του ΠΜΦ είναι διπλή: α) η δυνατότητά του να συγκροτεί πλουραλιστικές οπτικές σχετικά με το τι θεωρείται επιθυμητό, κάτι που επιτρέπει τη δημιουργία διμερών στόχων και οραμάτων και αναγνωρίζει τις πιθανές συγκλήσεις και συνεργασίες των μέτρων που μπορούν να χρησιμοποιηθούν ώστε να επιτευχθούν αυτά και β) η λειτουργικότητά του που αφορά την δημιουργία σεναρίων και μοντέλων σε πολλαπλές κλίμακες, και μπορεί να καθοδηγήσει τη χάραξη πολιτικών σε σχετικά επίπεδα, τελικά μπορεί να εφαρμοστεί σε διαφορετικά μέρη και οπτικές σχετικά με τη φύση. Για να καταφέρει η ανθρωπότητα να χτίσει ένα βιώσιμο μέλλον, είναι ζωτικής σημασίας να δημιουργηθεί ο χώρος για να ακουστούν ποικίλες οπτικές σχετικά με τη σχέση των ανθρώπων με τη φύση. Καθώς η παγκόσμια κοινότητα ξεκινά μία νέα διαδικασία δημιουργίας στόχων για την προστασία της βιοποικιλότητας, το ΠΜΦ μπορεί να χρησιμοποιηθεί ως ένα καθοδηγητικό εργαλείο για τη δημιουργία ποικίλων, επιθυμητών μελλόντων. सार: वैज्ञानिकों ने बार‐बार तर्क दिया है कि जैव विविधता की गिरावट को रोकने और संपोषणीयता (सस्टेनबिलिटी) लक्ष्यों को प्राप्त करने की खोज में साधन के रूप में परिवर्तनकारी, बहु‐विषयक वैश्विक परिदृश्यों की आवश्यकता है। इसे प्राप्त करने की दिशा में पहले कदम के रूप में, जैव विविधता और पारिस्थितिकी तंत्र सेवाओं पर अंतर‐सरकारी विज्ञान‐नीति प्लेटफ़ॉर्म (आई.पी.बी.ई.एस) के परिदृश्य और मॉडल विशेषज्ञ समूह में भाग लेने वाले शोधकर्ताओं ने एक पुनरावृत्त, सहभागिता प्रक्रिया के माध्यम से नेचर फ्यूचर्स फ्रेमवर्क (एन.एफ.एफ) का विकास किया। एनएफएफ एक हेयुरिस्टिक या स्वानुभविक साधन है जो त्रिकोण के रूप में प्रकृति के साथ मनुष्यों के विविध, सकारात्मक संबंधों को व्यक्त करता है। यह वांछनीय प्रकृति परिदृश्यों के निर्माण में अधिक विविध दृष्टिकोण को लगातार पहचान करने के लिए एक बाउन्ड्री ऑब्जेक्ट (एक वैचारिक साधन जो विभिन्न अभिनेताओं के बीच सहयोग और संवाद को सक्षम बनाता है और उपयोग और धारणा में अंतर की अनुमति देता है) के रूप में और कई पैमानों पर निरंतर प्रकृति परिदृश्यों को विकसित करने के लिए एक क्रियाशील ढांचे के रूप में इस्तेमाल किया जा सकता है। यहां, हम एनएफएफ को विकसित करने के लिए नियोजित तरीकों का वर्णन करते हैं और यह प्रकृति के लिए परिवर्तनकारी, बहु‐विषयक परिदृश्य बनाने के लिए एक लंबी अवधि की प्रक्रिया में कैसे फिट बैठता है। हम तर्क देते हैं कि एनएफएफ का योगदान दो गुना है: क) क्या वांछनीय है पर दृष्टिकोण की बहुलता रखने की क्षमता, जो संयुक्त लक्ष्यों और दूरदृष्टि के विकास को सक्षम बनाता है और इन दृश्यों को प्राप्त करने के लिए उपायों के संभावित संमिलन और तालमेल को पहचानता है और ख) विस्तृत परिदृश्यों और मॉडलों को विस्तृत करने के लिए के लिए इसकी बहु‐स्तरीय कार्यक्षमता जो प्रासंगिक स्तरों पर निर्णय लेने की सूचना दे सकती है, जिससे यह प्रकृति के विशिष्ट स्थानों और दृष्टिकोणों पर लागू होती है। यदि मानवता को समृद्धिशाली प्रकृति में निहित एक अधिक धारणीय और संपन्न भविष्य के अपने लक्ष्य को प्राप्त करना है, तो मानव‐प्रकृति संबंधों के अधिक बहुवचन दृष्टिकोणों के लिए स्वीकृति सुनिश्चित करना महत्वपूर्ण है। जैसा कि वैश्विक समुदाय जैव विविधता के लिए नए लक्ष्यों को विकसित करने के लिए तैयार है, एनएफएफ का उपयोग एक पथप्रदर्शक साधन के रूप में किया जा सकता है जो विविध, वांछनीय भविष्यो को संभव बनाने में मदद करता है। 概要: 生物多様性の劣化を阻止し、持続可能な社会を実現するためには、社会変革（transformative change）を考慮した、マルチスケールな地球規模シナリオの必要性が唱えられてきた。 その第一歩として、生物多様性及び生態系サービスに関する政府間科学‐政策プラットフォーム（IPBES）のシナリオ・モデル専門家グループの専門家らが、参加型・反復型シナリオ開発プロセスに着手し、Nature Futures Framework（NFF）を考案するに至った。 このNFFとは、良好かつ多様な自然と人との関係性を三角形の形で捉えたヒューリスティックなツールである。NFFは、望ましい自然の将来シナリオを構想する際に、多様な視点を絶え間なく取り込むためのバウンダリー・オブジェクトとして活用したり、マルチスケールでの将来シナリオを作成する際の一貫性を担保するための枠組みとして活用できる。 本稿では、著者らはNFFの開発に用いた手法、ならびにそれが社会変革を考慮したマルチスケールでの自然の将来シナリオを作成するための長期的なプロセスにどのように適合するかを解説する。著者らは、NFFには二つの利点があると考える。第一に、NFFを活用することで我々は「何が望ましい未来か」について複数の視点を持ち、共同の目標や将来ビジョンの作成を可能にし、それら目標やビジョンを達成するための施策の収斂や相乗効果を考慮できる点である。第二は、NFFはマルチスケールでのシナリオの作成やモデルの構築を助けることで、様々な場所や自然に関する価値観に適用可能であり、適切なレベルの意思決定に活用できる点である。 われわれ人類が豊かな自然に根ざした持続可能でより良い未来を築くためには、人と自然の関係性においてより多様な視点を持つことが不可欠である。生物多様性に関する新たな目標の策定に向けて国際社会が動き出す中、NFFは多様な望ましい未来を描くための羅針盤としての活用が期待できる。 Resumo: Cientistas têm argumentado repetidamente que cenários globais transformadores, orquestrados a diferentes escalas de governança, são ferramentas necessárias para reverter o declínio da biodiversidade e alcançar metas de sustentabilidade. Como primeiro passo para conseguir estes objetivos, os especialistas que participaram do grupo de cenários e modelos da Plataforma Intergovernamental em Biodiversidade e Serviços de Ecossistema (IPBES), desenvolveram um processo participativo e iterativo que levou ao desenvolvimento do Nature Futures Framework (NFF). O NFF é uma ferramenta heurística capaz de identificar relações positivas entre os seres humanos e a natureza representado na forma de um triângulo. Ele pode ser usado tanto para explorar continuamente perspectivas mais plurais na criação de cenários desejáveis para a natureza como também pode servir para criar consistência entre cenários a diferentes escalas de governança. Neste artigo descrevemos os métodos utilizados para desenvolver o NFF e mostramos o processo de longo prazo que é necessário para criar cenários desejáveis para a natureza que sejam capazes de ser transformadores a múltiplas escalas. O NFF apresenta duas grandes contribuições: a) a sua capacidade em estimular uma pluralidade de perspectivas sobre o que é desejável, permite o desenvolvimento de metas e visões conjuntas e reconhece a possível convergência e sinergias entre medidas para alcançá‐las; e b) a sua aplicabilidade a diferentes escalas de governança possibilita que a elaboração de cenários e modelos possa informar a tomada de decisões em níveis relevantes sendo aplicável em diferentes lugares com perspectivas específicas da natureza. Para que a humanidade alcance seu objetivo de um futuro mais sustentável e próspero, com valores enraizados na natureza, é fundamental abrir um espaço para perspectivas mais plurais das relações entre natureza e o Homem. À medida que a comunidade global se propõe a desenvolver novas metas para a biodiversidade, o NFF pode ser usado como uma ferramenta para ajudar a tornar possíveis futuros que são desejáveis e diversos. Аннотация: Учeныe нeoднoкpaтнo yтвepждaли, чтo тpaнcфopмaтивныe, мyльтимacштaбныe глoбaльныe cцeнapии нeoбxoдимы кaк инcтpyмeнт в дocтижeнии пpeкpaщeния yтpaты биopaзнooбpaзия и цeлeй ycтoйчивoгo paзвития. Пepвым шaгoм к paзpaбoткe тaкoгo инcтpyмeнтa cтaлo вcтyплeниe иccлeдoвaтeлeй из чиcлa гpyппы экcпepтoв пo cцeнapиям и мoдeллиpoвaнию Meжпpaвитeльcтвeннoй нayчнo‐пoлитичecкoй плaтфopмы пo биopaзнooбpaзию и экocиcтeмным ycлyгaм (MПБЭУ), в итepaциoнный пpoцecc c шиpoким вoвлeчeниeм yчacтникoв, кoтopый пpивeл к coздaнию Paмoчнoй кoнцeпции пepcпeктив бyдyщeгo пpиpoды (PКПБП). PКПБП ‐ этo эвpиcтичecкий инcтpyмeнт, зaпeчaтлeвaющий paзнooбpaзныe пoзитивныe взaимooтнoшeния чeлoвeкa c пpиpoдoй в oбpaзe тpeyгoльникa. Eгo мoжнo пpимeнять кaк в кaчecтвe гpaничнoгo oбъeктa для пocтoяннoгo oткpытия бoлee плюpaлиcтичecкиx пepcпeктив пpи coздaнии пpeдпoчтитeльныx cцeнapиeв измeнeния пpиpoды, тaк и в кaчecтвe paбoчeй ocнoвы для paзpaбoтки пocлeдoвaтeльныx cцeнapиeв измeнeния пpиpoды в paзличныx мacштaбax. B дaннoй пyбликaции мы пpeдcтaвляeм мeтoдикy paзpaбoтки PКBБП и тo, кaк этoт инcтpyмeнт впиcывaeтcя в дoлгocpoчный пpoцecc coздaния тpaнcфopмaтивныx мyльтимacштaбныx cцeнapиeв измeнeния пpиpoды. Mы yтвepждaeм, чтo PКПБП: a) oблaдaeт вoзмoжнocтями пpидepживaтьcя плюpaлиcтичнocти в oтнocишeнии тoгo, чтo в пepcпeктивax бyдyщeгo являeтcя жeлaeмым, и чтo пoзвoляeт paзpaбaтывaть coвмecтныe цeли и кoнцeпции, a тaкжe имeeт вoзмoжнocть кoнвepгeнции и cинepгии мep для дocтижeния этиx цeлeй; и б) eё мyльтимacштaбнaя фyнкциoнaльнocть для paзpaбoтки cцeнapиeв и мoдeлeй, кoтopыe мoгyт быть иcпoльзoвaны пpи пpинятии peшeний нa cooтвeтcтвyющиx ypoвняx, чтo дeлaeт eгo пpимeнимым в кoнкpeтныx мecтax и c yчeтoм кoнкpeтныx пepcпeктив, cвязaнныx c пpиpoдoй. Для тoгo, чтoбы чeлoвeчecтвo дocтиглo cвoeй цeли ‐ бoлee ycтoйчивoгo и блaгoпoлyчнoгo бyдyщeгo, кoтopoe пoлaгaeтcя нa пpoцвeтaющyю пpиpoдy, кpaйнe вaжнo oткpыть вoзмoжнocти бoлee плюpaлиcтичнoгo пpeдcтaвлeния пepcпeктив взaимooтнoшeний мeждy чeлoвeкoм и пpиpoдoй. Пocкoлькy миpoвoe cooбщecтвo cтaвит пepeд coбoй зaдaчy paзpaбoтки нoвыx цeлeй в oблacти биopaзнooбpaзия, PКПБП мoжeт иcпoльзoвaтьcя в кaчecтвe нaвигaтopa, пoмoгaющeгo paccмaтpивaть paзнooбpaзныe, жeлaмыe пepcпeктивы бyдyщeгo пpиpoды. Abstracta: Los científicos han argumentado repetidamente que los escenarios globales, transformadores y de escalas múltiples son necesarios como herramientas para afrontar la pérdida de biodiversidad y lograr los objetivos de sostenibilidad. Como un primer paso para lograrlo, el grupo de expertos en escenarios y modelos de la Plataforma Intergubernamental científico‐normativa en Biodiversidad y Servicios Ecosistémicos (IPBES) mediante un proceso iterativo, participativo desarrollaron el Marco de los Futuros de la Naturaleza (MFN). EL MFN es una herramienta heurística que captura las diversas relaciones positivas existentes entre los seres humanos y la naturaleza y se representa en la forma de un triángulo. Puede ser usado tanto como un objeto para generar perspectivas plurales en la creación de escenarios deseables de la naturaleza o como un marco para desarrollar escenarios de la naturaleza consistentes a través de escalas múltiples. Aquí, describimos los métodos empleados para desarrollar el MFN y como este se ajusta a un proceso de largo plazo para crear escenarios transformadores y a diferentes escalas para el futuro de la naturaleza. La contribución de los MFN persigue dos objetivos principales: a) la posibilidad de mantener una pluralidad de perspectivas en aquello que es deseable, lo que permite el desarrollo de un conjunto de objetivos y visiones reconociendo la posible convergencia y sinergias de las medidas para alcanzarlos y b) su funcionalidad a escalas múltiples para elaborar escenarios y modelos que puedan informar a los tomadores de decisiones a niveles relevantes, haciéndolo aplicable a través de perspectivas específicas sobre la naturaleza. Si la humanidad va a afrontar el objetivo de un futuro más sostenible y próspero basado en una naturaleza floreciente, es crítico dar lugar a perspectivas más plurales de las relaciones entre el ser humano y la naturaleza. Mientras la comunidad global esta desarrollando nuevos objetivos para la biodiversidad, le MFN puede ser utilizado como una herramienta de exploración que ayude a generar posibles futuros diversos y deseables para la naturaleza y las personas. Tɔfabɔ: Abɔdeɛ mu nyansapɛfoɔ tɔkɔ so kyerɛ sɛ nnoɔma a ɛde mpuntuo ba wiase afanan yɛ adeɛ a ɛdi mu akɔtene wɔ mfifideɛ ne mmoawa mpuntummerɛe ne wiase amaman mpanimfoɔ mpuntuo mmotae ma wiase afanan nyinaa. Na sɛdeɛ animdefoɔ bɛtumi ama anisoadehunu aba mu no, animdefoɔ kuo a ɛfa wiase amaman akandifoɔ kuo ahodoɔ a wɔakwadare wɔ abɔdeɛ mu nyansapɛ nhyiamu a ɛfa abɔdeɛ mu a ɛfa mfifideɛ ne mmoawa ho a IPBES nkabom kuo de wɔn nsa ahyɛ krataa ase ɛfa mpuntuo ne nnwuma a wɔbɛtumi ayɛ ama n'aboa abɔdeɛ mpuntuo. Abɔdeɛ mpuntuo yɛ akodeɛ bebree a ne botae ne sɛ ɛde nkabom a ɛfa sɛdeɛ nnipa bɛtumi atena asaase yi so a ɛmfa ɔhaw biara mma. Yɛbɛtumi nso de ayɛ adesua afasuo a ɛbɛboa yɛn dadaa nimdeɛ a ɛfa abɔdeɛ daakye adesua ho. Afei yɛbɛdɔ asukɔ wɔ nnoɔma ahodoɔ a yɛbɛtumi de abɔ abɔdeɛ mu nyansapɛ ne sɛdeɛ saa botae bɛtumi de nsakrae a ɛfa abɔdeɛ ho aba. Wɔ yɛn daadaa kasa mu no yɛtumi gye nkyim ɛfa abɔdeɛ mu nyansapɛ banbɔ ho a ɛbɛtumi de daadaa mfasoɔ abrɛ abɔdeɛ nyinaa. Sɛ nnipa bɛtumi anya abɔdeɛ ho mfasoɔ daadaa a, ɛsɛ yɛn sɛ yɛnya anisoadehunu ma nipa ne abɔdeɛ nkae no ho sɛdeɛ aman ahodoɔ mpanimfoɔ de ayɛ wɔn anisoadehunu sɛ wɔbɛboa ama nkabom aba nipa ne abɔdeɛ nkae no ntam no, abɔdeɛ mu nyansapɛ ho banbɔ bɛtumi ayɛ ade titire bi a ɛbɛtumi ama saa botae yi nyianaa aba mu. Реферат: Hayкoвцi нe єдинopaзoвo cтвepджyвaли, щo тpaнcфopмaтивнi, мyльтимacштaбнi глoбaльнi cцeнapiї нeoбxiднi як iнcтpyмeнт для дocягнeння пpипинeння втpaти бiopiзнoмaнiття i цiлeй cтaлoгo poзвиткy. Пepшим кpoкoм дo poзpoбки тaкoгo iнcтpyмeнтy cтaв вxiд дocлiдникiв з чиcлa гpyпи eкcпepтiв зi cцeнapiїв тa мoдeлювaння Miжypядoвoї нayкoвo‐пoлiтичнoї плaтфopми з бiopiзнoмaнiття тa eкocиcтeмниx пocлyг (MПБEП), в iтepaцiйний пpoцec з шиpoким зaлyчeнням yчacникiв, щo пpизвiв дo poзpoбки Paмкoвoї кoнцeпцiї пepcпeктив мaйбyтньoгo пpиpoди (PКПMП). PКПMП – цe eвpicтичний iнcтpyмeнт, щo фiкcyє piзнoмaнiтнi пoзитивнi вapiaнти взaємoвiднocин мiж людинoю тa пpиpoдoю в фopмi тpикyтникa. Йoгo мoжнa викopиcтoвyвaти як y якocтi гpaничнoгo oб'єктa для пocтiйнoгo вiдкpиття бiльш плюpaлicтичниx пepcпeктив пpи cтвopeннi бaжaниx cцeнapiїв змiни пpиpoди, тaк i y якocтi ocнoви для poзpoбки пocлiдoвниx cцeнapiїв змiни пpиpoди в piзниx мacштaбax. B цiй пpaцi ми пpeдcтaвляємo мeтoдикy poзpoбки PКПMП i тe, як цeй iнcтpyмeнт iнтeгpyєтьcя в дoвгocтpoкoвий пpoцec cтвopeння тpaнcфopмaтивниx мyльтимacштaбниx cцeнapiїв змiн пpиpoди. Mи cтвepджyємo, щo PКПMП: a) мaє влacтивicть дoтpимaння плюpaлicтичнocтi вiднocнo тoгo, щo в пepcпeктивax мaйбyтньoгo є бaжaним, i щo дoзвoляє poзpoбляти cпiльнi цiлi i кoнцeпцiї, a тaкoж мaє мoжливicть кoнвepгeнцiї тa cинepгiї зaxoдiв для дocягнeння цiлeй; i б) її мyльтимacштaбнa фyнкцioнaльнicть для poзpoбки cцeнapiїв i мoдeлeй, якi мoжливo викopиcтaти пpи пpийняттi piшeнь нa вiдпoвiдниx piвняx, щo нaдaє мoжливicть викopиcтaння в кoнкpeтниx мicцяx i з ypaxyвaнням кoнкpeтниx пepcпeктив, пoв'язaниx iз пpиpoдoю. Для тoгo, щoб людcтвo дocяглo cвoєї цiлi – бiльш cтaлoгo тa блaгoпoлyчнoгo мaйбyтньoгo, щo cпиpaєтьcя нa пpoцвiтaючy пpиpoдy, вкpaй вaжливo вiдкpити мoжливocтi бiльш плюpaлicтичнoгo yявлeння пepcпeктив взaємoвiднocин мiж людинoю тa пpиpoдoю. Ocкiльки cвiтoвa cпiльнoтa cтaвить пepeд coбoю зaдaчy poзpoбки нoвиx цiлeй в oблacтi oxopoни бiopiзнoмaнiття, PКПMП мoжe бyти викopиcтaнa в якocтi нaвiгaтopa, щo дoпoмaгaє poзглядaти бiльш piзнoмaнiтнi, бaжaнi пepcпeктиви мaйбyтньoгo пpиpoди. Áljẹbrà: Awon onimo ijinle ti so ni aimoye igba pe opolopo iyipada oniruru isele ti o ka agbaye ni a ni lo fun idaduro ibaje ti a n ri ni ipinsiyeleye aye, ki a si le ni awon ibi‐afede ti o durosinsin. Ese kini ti a nilo lati gbe ni pe ijiroro larin awon onimo ti o kopa ninu oju isele won yi ati awon oloye lati oniruru ijoba ti o nise pelu imo ijinle ati eto imulo lori ipinsiyeleyele ati ise ilolupo eda. Iji roro yi ni o fun won ni itona si ati da Ilana Iseda Ojo iwaju ti a pe ni Nature Futures Framework (NFF). NFF yii je irin‐ise alamodaju ti o mu oniruru ibatan rere larin eda eniyan pelu iseda ni ona onigun meta. Ale loo bi alaa nnkan loorekoore lati si opo irisi ta fii seda oun ti o wunni ni iseda oniruru isele, tabi bi ilana sise fun itesiwaju isele ni iseda ti o se dede koja ipele oniruru. Nibe, a se apejuwe awon ona ti a gba gbe fi NFF lole ati bi o se jemo ilana ojo pipe to a fi da iyipada onipele isele fun iseda. A jiyan re pe ilowosi NFF wa ni abala meji: a) agbara re lati mu opolopo irisi lori oun ti o wuni, ti o ma n je ki a ni ifilele ibi‐afede ati iran lapapo, ki a si tun ri apejo to seese pelu ona amusisepo ti a le fi saseyori wonyi, ati b) ise sise onipele fun sise alaye isele ati awon awose ti a le fi so ipinnu ni awon ipele ti o baramu, eyi ti yio je ki a le loo koja awon ibi pato ati irisi lori iseda. Bi omo eniyan ba fe saseyori ibi‐afede ti yio pejo ati ojo iwaju oloro ninu iseda ti o gbe, o se koko ki a fi aye sile fun opolopo irisi lori ibatan omo eniyan ati iseda. Gegebi agbegbe agbaye ti pinu lati tesiwaju ninu ibi‐afede ti o pin si yeleyele, a le lo NFF gegebi irin ise atona ti yio je ki oniruru ojo iwaju ti o wuni di sise.